THE SOCIAL AND CLINICAL CHARACTERISTIC OF PATIENTS WITH THE ISOLATED GENITAL TUBERCULOSIS ASSOCIATED WITH INFERTILITY, THE ACTIVE AND CLINICALLY CURED TUBERCULOSIS OF RESPIRATORY ORGANS IN COMBINATION WITH PREGNANCY - A. V. Mordyk; G. A. Valeyeva; A. A. Yakovleva; L. V. Puzyreva (Бюллетень сибирской медицины, 2015)
Due to the high incidence of tuberculosis of women of reproductive age research at 270 patients was conducted. The group of research included women with infertility and genital tuberculosis, pregnant women with active tuberculosis of lungs, pregnant women with clinically cured tuberculosis of respiratory organs. Pregnant women with tuberculosis of lungs were more often from sociopathic families, had venereal diseases, HIV infection, hepatitises.